An economic evaluation of pneumococcal conjugate vaccines, PCV20 versus PCV15, for the prevention of pneumococcal disease in the Swedish pediatric population - Ann-Charlotte Fridh; Andreas Palmborg; An Ta; Donata Freigofaite; Sophie Warren; Johnna Perdrizet (Taylor & Francis Group, 2024)
In September 2023, 10-valent pneumococcal conjugate vaccine (PCV) was replaced by 15-valent PCV (PCV15) in Sweden's pediatric national immunization program. Following European approval of 20-valent PCV (PCV20) in March 2024, we assessed the cost-effectiveness of PCV20 versus PCV15, both under 2 + 1 schedule, among Sweden's pediatric population. A Markov state-transition model evaluated the economic and health benefits of PCV20 versus PCV15 among all ages over a 10-year time horizon. The base case adopted a Swedish payer perspective with an annual cycle length and 3.0% discount rate for costs and outcomes. Country-specific data informed population size, epidemiology, costs, and quality of life estimates. PCV15/PCV20 effect estimates were informed by PCV13 clinical effectiveness and impact studies plus PCV7 efficacy studies. Sensitivity analyses evaluated model robustness, including PCV20 under a 3 + 1 schedule. PCV20 was associated with higher quality-adjusted life year gains versus PCV15, averting an estimated 3,116 invasive pneumococcal disease cases 21,109 inpatient pneumonia cases, 6,618 outpatient pneumonia cases, and 36,209 otitis media cases, plus 3,281 pneumococcal disease-related deaths. PCV20 yielded substantial cost savings exceeding 5.4 billion SEK over a 10-year time horizon, primarily attributed to reduced direct medical costs due to improved health outcomes compared with PCV15. The findings confirmed the dominance of PCV20 in the base case, which remained robust across deterministic and probabilistic sensitivity analyses as well as scenario assessments. PCV20 was the dominant strategy versus PCV15 over 10 years. The broader serotype coverage of PCV20 suggests superior clinical and economic advantages over PCV15, warranting inclusion in Sweden's pediatric immunization program.